Analytical political economy - Veneziani, Roberto, 1972-; Zamparelli, Luca (Surveys of recent research in economics., 2018)
"Offering a unique picture of recent developments in a range of non-conventional theoretical approaches in economics, this book introduces readers to the study of Analytical Political Economy and the changes within the subject. Includes a wide range of topics and theoretical approaches that are critically and thoroughly reviewed Contributions within the book are written according to the highest standards of rigor and clarity that characterize academic work Provides comprehensive and well-organized surveys of cutting-edge empirical and theoretical work covering an exceptionally wide range of areas and fields Topics include macroeconomic theories of growth and distribution; agent-based and stock-flow consistent models; financialization and Marxian price and value theory Investigates exploitation theory; trade theory; the role of expectations and animal spirits on macroeconomic performance as well as empirical research in Marxian economics"--